2003
DOI: 10.2136/sssaj2003.1909
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Acidification Causes Soil Base‐Cation Depletion at the Bear Brook Watershed in Maine

Abstract: There h concern that changes i n atmospheric deposition, climate, or land use have altered the biogeochemistry o f forests causing soil base-cation depletion, particularly C e The Bear Brook Watershed i n Maine (BBWM) is a paired watershed experiment with one watershed subjected to elevated N and S deposition through bimonthly additions of (NH,)aO,.Quantitative soil excavations i n 1998 measured soil pools of exchangeable base cations9 yr after treatments began. Stream sampling at the weirs on a weekly and eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
138
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 165 publications
(152 citation statements)
references
References 71 publications
8
138
2
Order By: Relevance
“…Many streams in the northeastern U.S. exhibit long-term trends of declining Ca concentrations (HUNTINGTON 2000). Streamwater Ca concentrations may be declining due to decreases in deposition of both sulfate and Ca (LYNCH et al 2000) as well as decreases in exchangeable soil Ca (LAWRENCE et al 1999;LIKENS et al 1996;FERNANDEZ et al 2003). These findings indicated that both base cation depletion and stream water chemistry were related to acid deposition in this area.…”
Section: Base Cation Depletion In North American Forestsmentioning
confidence: 93%
“…Many streams in the northeastern U.S. exhibit long-term trends of declining Ca concentrations (HUNTINGTON 2000). Streamwater Ca concentrations may be declining due to decreases in deposition of both sulfate and Ca (LYNCH et al 2000) as well as decreases in exchangeable soil Ca (LAWRENCE et al 1999;LIKENS et al 1996;FERNANDEZ et al 2003). These findings indicated that both base cation depletion and stream water chemistry were related to acid deposition in this area.…”
Section: Base Cation Depletion In North American Forestsmentioning
confidence: 93%
“…3 and 4). These conditions are common in tropical forest ecosystems (Krusche et al, 2003;Vogt et al, 2006;Quesada et al, 2010), and contrast sharply with most temperate ecosystems, wherein exchangeable base cations generally dominate soil cation pools (Watmough & Dillon, 2003;Fernandez et al, 2003;Högberg et al, 2006 …”
Section: Acidification Characteristics Of Tropical Forest Soilmentioning
confidence: 99%
“…Over decadal timescales, numerous studies have shown that N fertilization and acid deposition can lead to declines in soil extractable cations (Hogberg et al 2006;Huntington 2005;Saarsalmi and Malkonen 2001), reduced foliar cation concentrations (Elvir et al 2005;Minocha et al 2000), and watershed-scale cation export (Fernandez et al 2003), although some sites show no change in cation cycling (Ingerslev et al 2001;Nilsen 2001;Nohrstedt 2001;Yanai et al 1999). Overall, a meta-analysis of 107 primarily temperate and northern sites showed that N additions generally increase mobilization of exchangeable base cations into soil solution and stream water, with parallel declines in soil extractable cations (Lucas et al 2011).…”
Section: Introductionmentioning
confidence: 99%